Orthodontic strain affects the Hippo-pathway effector YAP concomitant with proliferation in human periodontal ligament fibroblasts. (17th March 2017) - Huelter-Hassler, Diana; Tomakidi, Pascal; Steinberg, Thorsten; Jung, Britta A.
Summary: Objectives: During orthodontic tooth movement (OTM), human periodontal ligament fibroblasts (hPDLFs) sense, and respond to mechanical forces. Since the molecular constituents involved in these processes are not fully elucidated, the objective of the present study was to identify further key molecules of the cellular strain response. Materials and Methods: Primary hPDLFs were strained with a static equiaxial strain of 2.5 per cent for 15 minutes, 1 hour, 6 hours, and 24 hours. Western blot (WB) and indirect immunofluorescence (IIF) analyses were performed to investigate the quantity and activation state of proteins involved in mechanotransduction, namely extracellular signal-regulated kinase (ERK) 1/2 and yes-associated protein (YAP). On the cell behavioural level, proliferation was assessed by the marker of proliferation KI-67. Results: In response to the applied strain, an early decline of phosphorylated and thus activated ERK1/2 was observed, followed by a mild recovery. Furthermore, both WB and IIF analyses revealed a modulation of nuclear YAP localisation. Concomitant with the modulation of YAP, the applied strain evoked an early increase in nuclear KI-67 amount, followed by a continuous decrease. Limitations: Consecutive studies will focus on scrutinising the suggested relationship between YAP and proliferation in response to static strain. Conclusions: Our findings provide evidence of ERK1/2 and YAP being biomechanically responsive molecular players in the context of OTM, among which YAP rather than ERK1/2 seems to be mechanistically interrelated with proliferation. Furthermore, the molecular and cell behavioural strain-induced early modulations may point to an involvement of the investigated molecules in the initial and the following lag phase of OTM.